Emergency surgery for colorectal cancer does not result in nodal understaging compared with elective surgery - Patel, Sunil Vijay (Canadian Medical Association, 2014)
BACKGROUND: It has been suggested that inadequate lymph node harvest may result in pathologically understaged or indeterminate staging of patients with colorectal cancer (CRC). We compared the adequacy of nodal staging in patients undergoing emergency surgery compared with elective surgery for CRC. METHODS: Using a prospectively collected CRC surgery database at a tertiary care centre, we performed a cohort study. The mean number of lymph nodes harvested and the proportion of patients who had inadequate staging (< 12 nodes harvested) were compared between emergency and elective surgery cohorts. Our analysis was adjusted for tumour site, type of resection, surgical training and pathologic stage. RESULTS: A total of 1279 of 1356 (94%) enrolled patients had nodal data available for analysis; 161 (13%) patients had emergency surgery and 1118 (87%) had elective surgery. The mean number of nodes removed was higher in the emergency surgery group (mean difference +2.8, 95% confidence interval [CI] 0.6–5.1, p = 0.012). The proportion of patients with inadequate nodal staging did not differ between groups (emergent 16%, elective 17%, p = 0.79). The odds of adequate nodal staging, adjusting for site, type of resection, training and stage was no different between groups (OR 0.80, 95% CI 0.47–1.35, p = 0.41). CONCLUSION: The evidence does not support the common belief that emergency surgery is more commonly understaged in CRC. Our data suggest emergency surgery resulted in a significant increase in the average number of nodes harvested, with no difference in inadequate nodal staging.